So, the event "rolling an even number on the die and drawing an even-numbered card" corresponds to exactly one outcome of the experiment.
In this experiment, there are six possible outcomes from rolling the die (1, 2, 3, 4, 5, or 6) and ten possible outcomes from drawing a card (1, 2, 3, 4, 5, 6, 7, 8, 9, or 10).
To find the total number of outcomes, we multiply the number of outcomes from rolling the die by the number of outcomes from drawing a card: [tex]6 (outcomes from the die) * 10 (outcomes from the card) = 60 possible outcomes.[/tex]
An event corresponds to a specific combination of rolling the die and drawing a card. For example, rolling a 1 on the die and drawing a card numbered 1 is one possible outcome.
Now, let's consider the definition of an event that corresponds to exactly one outcome of the experiment:
An event where the die shows an even number (2, 4, or 6) and the card drawn is also even (2, 4, 6, 8, or 10) would correspond to exactly one outcome of the experiment.
For example, if the die rolls a 2 and the card drawn is a 4, this combination uniquely identifies one outcome of the experiment.
(3a-2b)(3a+3b) so this is foil but i always get messed up on it does anyone now how to do it
Answer:
9a^2 + 3ab - 6b^2
Step-by-step explanation:
(3a-2b)(3a+3b)
First term of each grouping is 3a and 3a.
Multiply those you get 9a^2.
Outer term of each grouping is 3a and 3b.
Multiply those you get 9ab.
Inner term of each grouping is -2b and 3a.
Multiply those you get -6ab.
Last term of each grouping is -2b and 3b.
Multiply those you get -6b^2.
Add up all your products from above.
9a^2+9ab+-6ab+-6b^2
There are like terms here. The 9ab+-6ab which is 3ab.
So you can write your expression now as:
9a^2 + 3ab +-6b^2
9a^2 + 3ab - 6b^2
Step-by-step explanation:
[tex]\text{Use FOIL}\ (a+b)(c+d)=ac+ad+bc+bd:\\\\(3a-2b)(3a+3b)\\\\=(3a)(3a)+(3a)(3b)+(-2b)(3a)+(-2b)(3b)\\\\=9a^2+9ab-6ab-6b^2\qquad\text{combine like terms}\\\\=9a^2+3ab-6b^2[/tex]
HELP PLEASE!
simplify
(2x^3y)^3 / (4xy^2)^2(xy^3)
Answer:
[tex]\large\boxed{\dfrac{(2x^3y)^3}{(4xy^2)^2(xy^3)}=\dfrac{x^6}{2y^4}}[/tex]
Step-by-step explanation:
[tex]\dfrac{(2x^3y)^3}{(4xy^2)^2(xy^3)}\qquad\text{use}\ (ab)^n\ \text{and}\ (a^n)^m=a^{nm}\\\\=\dfrac{2^3(x^3)^3y^3}{4^2x^2(y^2)^2xy^3}\qquad\text{cancel}\ y^3\\\\=\dfrac{8x^{(3)(3)}y^3\!\!\!\!\!\diagup}{16x^2y^{(2)(2)}xy^3\!\!\!\!\!\diagup}\\\\=\dfrac{8\!\!\!\!\diagup^1x^9}{16\!\!\!\!\!\diagup_2x^2y^4x}\qquad\text{use}\ a^na^m=a^{n+m}\\\\=\dfrac{x^9}{2x^{2+1}y^4}\\\\=\dfrac{x^9}{2x^3y^4}\qquad\text{use}\ \dfrac{a^n}{a^m}=a^{n-m}\\\\=\dfrac{x^{9-3}}{2y^4}\\\\=\dfrac{x^6}{2y^4}[/tex]
Given the functions, F (x)=√(2x-5) and g(x) = 3x 2 + 2, perform the indicated operation. f(g(x))
Answer:
[tex]f(g(x)) =\sqrt{6x^2-1}[/tex]
Step-by-step explanation:
Given
f(x) = √2x-5
and
g(x) = 3x^2+2
We have to find the composition of both function
f(g(x)) means that we have to put function g in place of x in function f.
[tex]f(g(x))= \sqrt{2*g(x)-5}\\ =\sqrt{2(3x^2+2)-5}\\=\sqrt{6x^2+4-5}\\=\sqrt{6x^2-1}[/tex]
..
The composite function f(g(x)) is given by f(g(x)) = √(6x^2 - 1).
To find the composite function f(g(x)), you need to substitute the expression for g(x) into the function f(x). Here's how you can do it step by step:
Start with the function g(x):
g(x) = 3x^2 + 2
Now, substitute this expression into the function f(x):
f(g(x)) = √(2(3x^2 + 2) - 5)
Simplify the expression inside the square root:
f(g(x)) = √(6x^2 + 4 - 5)
Further simplify the expression inside the square root:
f(g(x)) = √(6x^2 - 1)
So, the composite function f(g(x)) is given by:
f(g(x)) = √(6x^2 - 1)
for such more question on composite function
https://brainly.com/question/10687170
#SPJ3
Find the sixth term of the
geometric sequence, given the
first term and common ratio.
a1=5 and r=3/2
Answer:
[tex]\frac{1215}{32}[/tex]
Step-by-step explanation:
The n th term of a geometric sequence is
[tex]a_{n}[/tex] = a₁ [tex](r)^{n-1}[/tex], hence
[tex]a_{6}[/tex] = 5 × [tex](\frac{3}{2 )} ^{5}[/tex] = 5 × [tex]\frac{243}{32}[/tex] = [tex]\frac{1215}{32}[/tex]
The sixth term of the geometric sequence is 1215/32 given that the first term a₁=5 and common ratio r=3/2. This can be obtained by using formula for nth term of the geometric sequence.
What is a geometric sequence?
Sequence is s collection of objects in a particular order and repetitions are allowed.
Geometric Sequence:
a, ar, ar¹, ..., arⁿ⁻¹ is a geometric sequence, where a is the first term, r is the common ratio and arⁿ⁻¹ is the nth term.
Calculate the sixth term:From the definition, nth term of a geometric sequence is arⁿ⁻¹.
Given that, a₁=5 and r=3/2
To find sixth term, put n=6 ⇒ arⁿ⁻¹=(5)(3/2)⁶⁻¹
=(5)(3/2)⁵
=5(3⁵/2⁵)
=5×(243/32)
=1215/32
Hence the sixth term of the geometric sequence is 1215/32 given that the first term a₁=5 and common ratio r=3/2.
Learn more about geometric sequence here:
brainly.com/question/2959141
#SPJ2
In the table, the parts of strawberry concentrate and the parts of water to prepare a strawberry drink are given. There is a proportional relationship between these two quantities. Find the value of x.
Parts of Water 3 9 36
Parts of Concentrate 1 3 x
Answer:
12
Step-by-step explanation:
[tex]\frac{Parts of Water}{Parts of Concentrate} =3[/tex]
3/1=3
9/3=3
36/12=3
Which of the following is not an integer?
0.5
-22
75
0
Answer:
0.5
Step-by-step explanation:
Integers will not include decimals.
Integers are numbers you count with or the opposite of the counting numbers and also 0.
.5 is not a counting number (or the opposite of one or 0) so this is the one that isn't an integer.
Final answer:
Among the options provided, 0.5 is not an integer because it is a decimal number, whereas -22, 75, and 0 are all whole numbers and thus integers.
Explanation:
The question is asking to identify which of the given numbers is not an integer. An integer is defined as any whole number, including negatives, zero, and positive whole numbers. Therefore, out of the options given (0.5, -22, 75, 0), the number 0.5 is not an integer as it is not a whole number but a decimal.
What is the product of the complex number z1 and it’s conjugate? PLEASE HELP GRAPH in picture
Answer:
The product is 25
Step-by-step explanation:
we know that
The complex number z1 is equal to
z1=(-4-3i)
we know that
To find the complex conjugate of (-4 - 3i) we change the sign of the imaginary part
so
The conjugate is equal to (-4+3i)
therefore
[tex](-4-3i)(-4+3i)=16-9(-1)=25[/tex]
Answer:
[tex](-4-3i) (- 4 + 3i) = 25[/tex]
Step-by-step explanation:
Notice in the graph that z1 has a real component of -4 and an imaginary component of -3.
Then we know that:
[tex]z_1 = -4-3i[/tex]
By definition for an imaginary number of the form [tex]a-bi[/tex] its conjugate will always be the number [tex]a + bi[/tex]
So the conjugate of [tex]z_1[/tex] is:
[tex]-4 + 3i[/tex]
The product of both numbers is:
[tex](-4-3i) (- 4 + 3i) = 16-12i + 12i-9i ^ 2\\\\(-4-3i) (- 4 + 3i) = 16-9 (-1)\\\\(-4-3i) (- 4 + 3i) = 16 + 9\\\\(-4-3i) (- 4 + 3i) = 25[/tex]
what is 6/7divided into 3/14 plz helppp meh
Answer:
4
Step-by-step explanation:
6/7 divided by 3/14 is 4.
Find common denominators.
6/7 would be changed into 12/14.
3/14 would stay the same because its denominator is already 14.
12/3 = 4
Therefore, 6/7 divided by 3/14 is 4.
Answer:
The answer is 4
Step number one use the butterfly method:
6 14
-- ×---- =84/21
7 3
Step 2: Divide since it's improper
84÷21=4
4 21
-- × --- =4
1 21
what is the coefficient of x^3 in the expansion of (2x-3)^5?
A) -5
B) 10
C) -120
D) -360
E) 720
Answer:
309
Step-by-step explanation:
(2x-)^5
step 1
1 5 10 10 5 1
step 2
1(2x¹-3^0) 5(2x²-3^5) 10(2x³-3^4)
10(2x^4-3³) 5(2x^5-3²)
1(2x^0-3¹)
step 3
(2x) (10x²-243) (20x³-81) (20x^4-27)
(10x^5-9) (2-3)
step 4
2 -243-61-7 +1 -1=309
The coefficient of [tex]x^3[/tex] in the expansion of [tex](2x-3)^5[/tex] is 720
The correct answer is an option (E)
What is coefficient?"It refers to a number or quantity placed with a variable."
What is variable?"The alphabetic character that expresses a numerical value."
What is an expression?"It is a mathematical expression which consists of numbers, variables and mathematical operations."
Formula for [tex](a-b)^3[/tex]" [tex](a-b)^3=a^3-3a^2b+3ab^2- b^3[/tex] "
Formula for [tex](a-b)^2[/tex]" [tex](a-b)^2=a^2-2ab+b^2[/tex] "
For given question,
We have been given an expression [tex](2x-3)^5[/tex]
We need to expand given expression.
[tex](2x-3)^5\\\\= (2x-3)^3\times (2x-3)^2\\\\=[(2x)^3-3(2x)^23+3(2x)(3)^2- 3^3]\times ((2x)^2-2(2x)(3)+3^2)\\\\=[8x^3-36x^2+54x-27]\times [4x^2-12x+9]\\\\=-243+810x-1080x^2 +720x^3-240x^4+32x^5\\\\=32x^5-240x^4+720x^3-1080x^2+810x-243[/tex]
Therefore, the coefficient of [tex]x^3[/tex] in the expansion of [tex](2x-3)^5[/tex] is 720
The correct answer is an option (E)
Learn more about the coefficient here:
https://brainly.com/question/13431100
#SPJ2
point O is the center of this circle. What is the m<CAB
A). 55°
B). 48°
C). 45°
D). 35°
Answer:
B
Step-by-step explanation:
The angle on the circumference is half the angle subtended at the centre by the arc CB, that is
∠CAB = 0.5 × ∠COB = 0.5 × 96° = 48° → B
m∠CAB is 48° given that point O is the center of the circle and ∠COB is 96°. This can be obtained by using the circle theorem.
What is circle theorem ?Circle Theorem: The angle subtended by an arc at the center is double the angle subtended by it at any point on the remaining part of the circle.Given that, ∠COB = 96°
By applying Circle theorem, we can say that
∠COB = 2∠CAB
96° = 2∠CAB
∠CAB = 96°/2 = 48°
∠CAB = 48°
Hence m∠CAB is 48° given that point O is the center of the circle and ∠COB is 96°.
Learn more about circle theorem here:
brainly.com/question/17158173
#SPJ2
IXL/HELP!!
What is the answer
Answer:
20.6
Step-by-step explanation:
28.6×20.6=589.16
Answer:
20.6
Step-by-step explanation:
Area of a rectangle = base times height
A = bh
Substitute in what we know
589.16 = 28.6 * h
Divide each side by 28.6
589.16/28.6 = 28.6h/28.6
20.6=h
What is the equation of the line that is parallel to the given line and passes through the point (-3, 2)?
4x + 3y = -6
Step-by-step explanation:
graph the following {(x,y): x + y = 5}
For this case we have the following function:
[tex]y = 5-x[/tex]
We look for the points of intersection with the x axis, doing y = 0
[tex]0 = 5-x\\x = 5[/tex]
We look for the points of intersection with the y axis, doing x = 0
[tex]y = 5-0\\y = 5[/tex]
We can also observe that the slope is -1.
[tex]y = mx + b\\y = -x + 5[/tex]
Answer:
See attached image
Arnold has x amount of money in
his checking account. He spends
$12.36 for breakfast but has at least
$31.24 left in his account. How much
money did he have originally?
Answer:
43.60
Step-by-step explanation:
12.36+31.24
If X || Y and Y || Z then___
Answer:
X is parallel to Z
X || Z
Step-by-step explanation:
This is called the transitive property.
It says something like:
If f is related to g and g is related to h, then f is related to h.
The parallel relationship is transitive.
That is,
if X is parallel to Y and Y is parallel to Z, then X is parallel to Z.
use elimination method to solve the system of equations. Choose the correct order pair. -x+5y=-4 4x+4y=16
Answer:
(4,0)
Step-by-step explanation:
So we have the system:
-x+5y=-4
4x+4y=16
--------------
We are asked to solve this for elimination.
We aren't totally setup for elimination though.
Both equations are in the same form, the form being ax+by=c form, so we are good there.
Now the other requirement is one the columns that contain variables need to be opposites (you will add) or same (you will subtract).
I'm going to multiply the first equation by 4. The reason I'm going to do this is because the first column will contain -4x and 4x. Those are opposites. When you add opposites, you get 0 (they cancel).
So applying the multiplication of 4 to first equation gives:
-4x+20y=-16
4x+ 4y=16
----------------- Add the equations now.
0x+24y=0 Again this is called elimination, because we made it to where a variable is canceled when combining the equations.
0x+24y=0
0+ 24y=0
24y=0
Divide both sides by 24:
y=0
So using one of the equations (you only need one of them) along with the y=0, let's find x.
I'm going to go with -x+5y=-4 with y=0.
Plugging in the 0 for y gives us:
-x+5y =-4
-x+5(0)=-4
-x+ 0 =-4
-x =-4
Multiply both sides by -1:
x =4
The solution is (x,y)=(4,0).
ANSWER
The ordered pair is
(4,0)
EXPLANATION
To solve a simultaneous equation using the elimination method means making the coefficient of one of the variables the same. We then add or subtract to eliminate that variable.
The given system has equations:
[tex] - x + 5y = - 4...(1)[/tex]
[tex]4x + 4y = 16...(2)[/tex]
Divide the second equation by 4
[tex]x + y = 4...(3)[/tex]
Add equation (1) and (3) to eliminate x.
[tex] \implies \: 5y + y = - 4 + 4[/tex]
[tex] \implies \: 6y = 0[/tex]
[tex] \implies \: y = \frac{0}{6} = 0[/tex]
Put
[tex]y = 0[/tex]
into the first equation to get:
[tex] - x + 5 \times 0 = - 4[/tex]
[tex] - x = - 4[/tex]
[tex] \therefore \: x = 4[/tex]
The ordered pair is
(4,0)
Which of these is a trinomial?
A. 2x-7
B. 2x2 - 7/3 + 14
c. 2y2 + 7y
D. 5xy
Answer:
the answer is D
Step-by-step explanation:
a is not it has a negative
a b is not it has an equation in it
so that leaves it to see and d c does not work
because it has to have two variables per one number
NEED HELP ASAP PLEASE
Find the ratio of the known sides and calculate X.
1. The smaller triangle is half the size of the lager one:
6/12 = 1/2
10/12 = 1/2
This means x is half the length of 16
x = 16/2 = 8
2. 18/30 = 3/5
9/15 = 3/5
This means x is 3/5 of 25
x = 25 * 3/5 = 15
3. 32/24 = 1 1/3
16 /12 = 1 1/3
X is 1 1/3 times the length of 21
x = 21 x 1 1/3
x = 28
4. 12/15 = 4/5
20/25 = 4/5
x is 4/5 the length of 40
x = 40 * 4/5
x = 32
Find one positive and one negative angle coterminal with an angle of [tex]\frac{11pi}{8}[/tex].
idk how to do the pi sign
Answer:
see explanation
Step-by-step explanation:
Co terminal angles are angle ± 2π, that is
[tex]\frac{11\pi }{8}[/tex] + 2π
= [tex]\frac{11\pi }{8}[/tex] + [tex]\frac{16\pi }{8}[/tex] = [tex]\frac{27\pi }{8}[/tex]
and
[tex]\frac{11\pi }{8}[/tex] - 2π
= [tex]\frac{11\pi }{8}[/tex] - [tex]\frac{16\pi }{8}[/tex] = - [tex]\frac{5\pi }{8}[/tex]
3Q + 4T = 26. P=2T=3Q l. What is 6P?
The answer is 52 but I don’t understand how they got this answer
Step-by-step explanation and answer:
The given equations P=2T=3Q can be split up into
P=2T..................(1)
P=3Q................(2)
since they are all equal.
Rewrite the given equation
3Q + 4T = 26 .............(3)
as
3Q + 2(2T) = 26 ...........(4)
and substitute (1) and (2) into (4)
P + 2(P) = 26 .................(5)
Multiply (5) by two to get
6P = 2*26 = 52 ..............(6)
as given.
Answer:
see explanation
Step-by-step explanation:
Given P = 2T = 3Q, then
3Q + 4T = 26 can be expressed as
P + 2P = 26
3P = 26 ( multiply both sides by 2 )
6P = 52 ← as required
find the value of x
An outside angle is equal to the sum of the two opposite inside angles.
The triangle has an outside angle of 98, it's two opposite inside angles are given as 32 and X.
To find X, subtract 32 from 98.
X = 98 - 32 = 66
The answer is B.
How many teams are represented by every color in the pie chart shown
Answer: 5
times are properly represented on the chart, the other represents other possible colored teams
Step-by-step explanation:
There are 6 colors in the key, indicating there are at least 6 teams. But we only have a formal data set of 5 of those colors, therefore representing 5 teams.
The number of teams represented by each color in the pie chart are as follows:
Black: 24%, Navy blue: 21%, White: 19%, Gray: 16%, Maroon: 8%, Other: 12%
The pie chart shows that the dominant uniform color in the dataset is black, with 24% of teams represented by that color. This is followed by navy blue (21%), white (19%), gray (16%), and maroon (8%). The remaining 12% of teams are represented by a variety of other colors.
Here is a table showing the number of teams represented by each color:
Color | Number of teams
Black 24%
Navy blue 21%
White | 19%
Gray | 16%
Maroon | 8%
Other | 12%
Please note that the pie chart does not specify the total number of teams in the dataset, so it is not possible to say exactly how many teams are represented by each color. However, we can estimate that approximately 24% of the teams are black, 21% are navy blue, 19% are white, 16% are gray, 8% are maroon, and 12% are represented by a variety of other colors.
For such more questions on color
https://brainly.com/question/17141025
#SPJ12
Choose the equation that represents the line that passes through the point (6,-3,) and has a slope of 1/2
Answer:
[tex]y=\frac{1}{2}x-6[/tex]
Step-by-step explanation:
The general equation of a line: [tex]y = ax+b[/tex]
In our case a is given
[tex]a=\frac{1}{2}[/tex]
Now we plug in for a and we get:
[tex]y=\frac{1}{2}*x+b[/tex]
Now we plug in our coordinates into this equation and we solve for b
[tex]-3=\frac{1}{2}*6+b\\b = -6[/tex]
So the equation of the line is [tex]y=\frac{1}{2}x-6[/tex]
Answer:
[tex]y=\frac{1}{2}x-6[/tex]
Step-by-step explanation:
Since the Inclination of the line was already given to us. Let us use Inclination of line formula:
[tex]m=\frac{y-y_0}{x-x_0}[/tex]
Plugging it in those values then we have the equation of the line:
[tex]\frac{1}{2}=\frac{y+3}{x-6}[/tex]
Rewriting, multiplying both sides
2y+6=x-6
2y=x-12 Rearranging
[tex]y=\frac{1}{2}x-6[/tex]
What are the solutions of the equation x^4+ 95x^2-500=0? Use factoring to solve
Answer:
x^4+100x^2-5x^2-500=0
x^2(x^2+100)-5(x^2+100)=0
(x^2+100)(x^2-5)=0
from first expression
x^2+100=0
x^2=-100
x= root under -100
Therefore x=-10
from next expression
x^2-5=0
x^2=5
Or x=2.23
Step-by-step explanation:
Answer:
x = ± sqrt(5)
x = ±10i
Step-by-step explanation:
x^4+ 95x^2-500=0
What two numbers multiply to -500 and add to 95
-5 * 100 = -500
-5 +100 = 95
(x^2 - 5) (x^2 + 100) = 0
Using the zero product property
x^2 -5 =0 x^2 +100 =0
x^2 -5+5 =0 x^2 +100-100 = 0-100
x^2 =5 x^2 = -100
Take the square root of each side
x = ± sqrt(5) x = imaginary numbers
x = ±10i
Ella is stuffing envelopes. She has 48 red pages, 25 white pages, and 84 blue pages. If she need to put 2 red pages, 1 white pages, and 4 blue pages in every envelope to make it complete, how many complete envelopes can she make?
Ella can make 21 complete envelopes with her available red, white, and blue pages, since the number of complete sets is limited by the blue pages.
Ella has 48 red pages, 25 white pages, and 84 blue pages. She needs to put 2 red pages, 1 white page, and 4 blue pages in every envelope. To find out how many complete envelopes she can make, we need to calculate the number of complete sets of pages she can create based on the quantity of each color she has and the number she needs for each envelope.
For the red pages: 48 red pages / 2 pages per envelope = 24 envelopes
For the white pages: 25 white pages / 1 page per envelope = 25 envelopes
For the blue pages: 84 blue pages / 4 pages per envelope = 21 envelopes
Since the number of envelopes is limited by the color with the least amount of complete sets, Ella can make 21 complete envelopes because she will run out of blue pages after the 21st envelope.
What is the missing term?
(10х — 4х2) - (7х + ?) = 3х – 6х2
(10х — 4х2) - (7х + ?) = 3х – 6х2
10x - 7x = 3x which is given,
Now you have -4x^2 - ? needs to equal -6x^2
write it as an equation:
-4x^2 - ? = -6x^2
To solve for ? add 4x^2 to each side:
-? = -2x^2
Multiply each side by -1:
? = 2x^2
Question 1
1 pts
Maureen worked 48 hours last week. Her hourly rate is $8.00. What was her salary, not
including overtime pay?
• 384.00
230.00
320.00
480.00
Answer:
$384.00
Step-by-step explanation:
Since $8..0 is 1 hour, just multiply 48 x 8! Hope this helps!
Answer:
320
Step-by-step explanation:
The reason that you 48* 8 is because the 48 has overtime included in it so you would only 40*8.
Which of the following is equivalent to
Answer:
[tex]x^{4}[/tex]
Step-by-step explanation:
[tex]\frac{x^{5}y^{2} }{xy^{2} }[/tex]
= [tex]x^{4}[/tex]
Question 1:
For this case we have the following expression:
[tex]\frac {x ^ 5y ^ 2} {xy ^ 2}[/tex]
We eliminate similar terms in the numerator and denominator:
[tex]\frac {x ^ 5} {x}[/tex]
By definition of division of powers of the same base we have to place the same base and subtract the exponents:
[tex]\frac {x ^ 5} {x} = x ^ {5-1} = x ^ 4[/tex]
ANswer:
Option D
Question 2:
For this case we must indicate which expression is not equal to 125.
We tested option A:
[tex]5 (\frac {5 ^ 3} {\frac {2} {5}}) ^ 2 =[/tex]
Simplifying we have:
[tex]5 (\frac {5 ^ 3 * 5} {2}) ^ 2 =\\5 (\frac {5 ^ 8} {4}) =\\\frac {5 ^ 9} {4}[/tex]
The expression is not equal to 125.
Answer:
option A
Solve.
{y=x−82x+3y=1
Use the substitution method.
(5, −3)
(4, −4)
(0, −8)
(2, −6)
Answer:
(5,-3) if the system is
y=x-8
2x+3y=1
Step-by-step explanation:
I think the system is to read:
y=x-8
2x+3y=1.
Please correct me if I'm wrong.
I'm going to plug 1st equation into 2nd equation giving me:
2x+3(x-8)=1 ->I replaced y with (x-8).
Distribute:
2x+3x-24=1
Combine like terms:
5x-24=1
Add 24 on both sides:
5x=25
Divide both sides by 5:
x=5
If y=x-8 and x=5, then y=5-8=-3.
The solution is (5,-3).
(5, −3) is the solution of given system of equations.
What is equation?"It is a mathematical statement which consists of equal symbol between two algebraic expressions."
What is a system of equations?"It is set of equations for which we find a common solution."
What is substitution method?"It is a method of solving system of equation we substitute the value of a variable found by one equation in the second equation."
For given question,
We have been given a system of equations.
y = x - 8 ..............(i)
2x + 3y = 1 ...............(ii)
We use substitution method to solve given system of equations.
Substitute the value of y from (i) to equation (ii).
⇒ x + 3(x - 8) = 1
⇒ 2x + 3x - 24 = 1
⇒ 5x = 1 + 24
⇒ 5x = 25
⇒ x = 5
Substitute above value of x in an equation (i)
⇒ y = 5 - 8
⇒ y = -3
So, the solution of given system of equations is x = 5 and y = -3
Therefore (5, -3) is the solution of given system of equations.
Learn more about the substitution method here:
https://brainly.com/question/14619835
#SPJ2
evaluate 3^-3 please explain
Answer:
D) 1/27
Step-by-step explanation:
The question is: 3^(-3).
Note that there is a negative sign in the number at the power place. This means that you must flip the number, and in this case, put it over 1. The rest is solved as usual:
3^-3 = 1/(3^3) = 1/(3 * 3 * 3) = 1/27
1/27, or D) is your answer.
~